Physical education and biopolitics in post-dictatorship Uruguay (1985-1990) - Rodrigo Piriz; Alexandre Vaz (Arizona State University, 2019)
This paper provides a discursive analysis of the four curricular programs of the Comisión Nacional de Educación Física (CNEF-Uruguay) of 1988, which are some of the fundamental documents of the policies in Physical Education in the first post-dictatorial quinquennium in Uruguay (1985-1990). We describe the conditions for the potential development of a physical education characterized by its ludic quality, exploring   the frequent references to recreation in the policies in Physical Education as a government strategy aimed at the regulation of the population. Then, we analyze the relationship between politics and the education of the body,  in light of the post-dictatorship policies and the policymakers attempt to distance themselves from the proposals developed in the dictatorial period. During the military-civic dictatorship in Uruguay (1973-1985); gymnastic displays and sporting events were exalted. In the return to democracy, physical  education policies took a more recreational form, although maintained the same spirit: the government of the population and the productive body.